Ferroconcrete-inspired design of a nonwoven graphene fiber fabric reinforced electrode for flexible fast-charging sodium ion storage devices. Issue 5 (20th January 2020) - Liu, Zexin; Zhang, Xin; Liu, Cai; Li, Dongyang; Zhang, Miaoxin; Yin, Fuxing; Xin, Guoqing; Wang, Gongkai
Abstract : Ferroconcrete-inspired graphene fiber nonwoven fabrics integrated with multi-functionalities for use as free-standing anodes/cathodes give superior performances as flexible sodium ion capacitors. Abstract : Flexible fast-charging sodium ion storage devices are poised to transform the future wearable electronics industry, if the materials used to build such devices can present a versatile integration. Herein, inspired by ferroconcrete, nonwoven graphene fiber (GF) fabric reinforced electrodes were successfully demonstrated in flexible sodium ion capacitors (SICs). For the fabrics, the functionalities of fast electron transport and an ion permeation network, a highly compatible electrode material host, an efficient capacity contributor, and a robust flexible framework are synergistically integrated. These were provided by the high conductivity of the graphene sheets, the tunable porosity of the GF, and the interlocked structure, compatibility with materials, and the surface capacitive contribution of the fabrics. The nonwoven fabrics hosted multi-dimensional active materials as the ferroconcrete electrode exhibits exceptional electrochemical and mechanical properties individually. The SICs can complete an entire charge–discharge process within 15 s. A digital LED and watch powered using the flexible SICs with superior volumetric performances (12 mW h cm −3 @37 mW cm −3, and 6 mW h cm −3 @1.9 W cm −3 ) proved the practical capability of our design. We believe that the proposed nonwoven GF fabrics and the ferroconcrete electrode structure will become a universal design, and shed new light on flexible fast-charging sodium ion storage devices.